2021
DOI: 10.1007/s40830-021-00319-0
|View full text |Cite
|
Sign up to set email alerts
|

Valence Electron Ratio for Design of Shape Memory Alloys with Desired Phase Transformation Temperatures

Abstract: Dependence of Phase transformation temperatures of TiPd-and TiPt-based shape memory alloys on Valence Electron Ratio (VER), number (ev/a), and average atomic number of the alloys (Z) are investigated. The alloys have medium numbers of valence electrons (6.6 ≤ ev/a ≤ 7.3) that are near 7 and a wide range of the average atomic number (Z = 25-54). The forward and reverse phase transformation temperatures, Ms and (As), increase with average atomic number of the alloys, respectively. Clear correlations between tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Zarinejad and co‐workers [ 52,53 ] found that transformation temperatures in multicomponent NiTi‐based SMAs are strongly correlated with valence electron ratio (VER), which is actually the ratio of the number of valence electrons ( e v ) to the total number of electrons ( e t ) of an alloy. For a multicomponent alloy containing N elements, VER can be calculated as follows [ 52,53 ] VER=evet=i=1Nfievii=1NfiZiwhere fi, Zi, and evi represent the atomic percentage, atomic number, and number of valence electrons of the i th element, respectively. Based on this correlation, Ms and As temperatures of martensitic transformation tend to decrease with increasing VER.…”
Section: Resultsmentioning
confidence: 99%
“…Zarinejad and co‐workers [ 52,53 ] found that transformation temperatures in multicomponent NiTi‐based SMAs are strongly correlated with valence electron ratio (VER), which is actually the ratio of the number of valence electrons ( e v ) to the total number of electrons ( e t ) of an alloy. For a multicomponent alloy containing N elements, VER can be calculated as follows [ 52,53 ] VER=evet=i=1Nfievii=1NfiZiwhere fi, Zi, and evi represent the atomic percentage, atomic number, and number of valence electrons of the i th element, respectively. Based on this correlation, Ms and As temperatures of martensitic transformation tend to decrease with increasing VER.…”
Section: Resultsmentioning
confidence: 99%
“…A small compositional change can cause a significant displacement of transformation temperatures. However, this displacement is usually associated with the e/a parameter, which corresponds to the average outer electrons [19]. In this (cooling scan) and A s and A f are the austenite start and austenite finish temperatures (heating scan).…”
Section: Thermal Analysismentioning
confidence: 99%
“…of the material, which are dependent on both composition and temperature, are the key parameters influencing the transformation temperatures. [27,36] Dependence of transformation temperatures of the matrix crystals of solid solutions in NiTi, [28][29][30][37][38][39][40] TiPd and TiPt, [41] TiAu, and TiIr [42] -based alloys and many other alloy systems [2,43] was shown to be influenced by the chemistry of the alloys and how the metallic bonding in them changes because of the chemical composition change. Hence, the correlation of mechanical properties of solid solutions with electron variables in several alloys/intermetallic systems was introduced.…”
Section: Doi: 101002/adem202200606mentioning
confidence: 99%
“…Hence, the correlation of mechanical properties of solid solutions with electron variables in several alloys/intermetallic systems was introduced. [29][30][31][37][38][39][40][41][42][43] Knowing that in ceramic materials, the localized valence electrons dominate the strengths of bonds and elastic properties, [44,45] it is of particular importance to study the electronic parameters of the ceramics.…”
Section: Doi: 101002/adem202200606mentioning
confidence: 99%